Strategi Pemasaran Online pada Masa Pandemi Covid-19 Dalam Penerimaan Peserta Didik di SMK Al Hafidz Leuwiliang Bogor - Ilma Rahima; Dedi Junaedi; Evinovita Evinovita (LPPM IAI Nasional Laa Roiba Bogor, 2021)
This study is intended to answer the following problems: 1) What is the online marketing strategy during the COVID-19 pandemic in accepting students at Al Hafidz Leuwiliang Vocational School? 2) What is the influence of the Al Hafidz Leuwiliang Vocational High School Online Marketing Strategy in accepting students during the covid 19 pandemic? These problems were discussed through research conducted at SMK Al HAfidz Leuwiliang where this madrasa was used as a source of data information to obtain portraits, descriptions, answers and results of marketing management strategies in order to increase student acceptance. In this case the data obtained by means of interviews, observation and documentation. All data will be analyzed descriptively, namely by pouring the results into sentences that are arranged in such a way that they can be neatly arranged sentences. The results of the study show that: 1) In the online marketing strategy at SMK Al Hafidz Leuwiliang implemented by every element in the school, this is because the marketing strategy planning implemented will be able to run more effectively and maximally. SMK Al Hafidz also uses three stages of online marketing strategy, namely: Segmentation; Namely consumer actions about the needs and wants both in the present and in the future , Targeting ; namely positive targeting in determining which areas will become customers of Al Hafidz Vocational School. Three villages are prioritized, namely Karacak, Karyasari and Cibitung villages, as well as Positioning; namely about how to establish a position to gain competitive advantage between educational institutions in Leuwiliang District. 2) The implementation of online marketing strategies does not have much effect on student acceptance. Because offline marketing still needs to be needed by the customer (prospective students). Keywords: Online Marketing, Strategy, Covid 19 Pandemic